Skalabilitas Signal to Noise Ratio (SNR) pada Pengkodean Video dengan Derau Gaussian - Agus Purwadi (Universitas Syiah Kuala, 2015)
In video transmission, there is a possibility of packet lost an d a large load variation on the bandwidth. These are the source of network congestion, which can interfere the communication data rate. This study discusses a system to overcome the congestion with Signal-to-noise ratio (SNR) scalability-based approach, for the video sequence encoding method into two layers, which is a solution to decrease encoding mode for each packet and channel coding rate. The goal is to minimize any distortion from the source to the destination. The coding system used is a video coding standards that is MPEG-2 or H.263 with SNR scalability. The algorithm used for motion compensation, temporal redundancy and spatial redundancy is the Discrete Cosine Transform (DCT) and quantization. The transmission error is simulated by adding Gaussian noise (error) on motion vectors. From the simulation results, the SNR and Peak Signal to Noise Ratio (PSNR) in the noisy video frames decline with averages of 3dB and 4dB respectively.